Mortality of therapeutic fish Garra rufa caused by Aeromonas sobria - Majtán, Juraj (Asian Pacific Tropical Medicine Press, 2012)
OBJECTIVE: To investigate a case of mass mortality of Garra rufa (G. rufa) from a fish hatchery farm in Slovakia. METHODS: Causative bacterial agent was swabbing out of affected fish skin area and subsequently identified using commercial test system. Antibiotic susceptibility was determined by the disk diffusion method. RESULTS: Infected G. rufa was characterized by abnormal swimming behaviour, bleeding of skin lesions and local haemorrhages. Despite of using recommended aquatic antibiotic treatment no improvement was achieved and Aeromonas sobria (A. sobria) was identified as a causative agent of fish mortality. Due to massive fish mortality, antibiotic susceptibility of pure isolated culture of A. sobria was evaluated employing eight antibiotics against human infections. A. sobria was resistant only against one antibiotic, namely ampicilin. CONCLUSIONS: These results indicate that A. sobria can act as a primary pathogen of G. rufa and may be a potential risk factor for immunodeficient or immunoincompetent patients during the ichthyotherapy.